Association of PD-1 and PDL-1 gene polymorphisms with colorectal cancer risk and prognosis - KARAALP, ATİLA; SÜSLEYİCİ, BELGİN (My University, 2022)
Background Programmed Cell Death-1 (PD-1) together with Programmed Death Ligand 1 (PDL-1) have crucial roles in anti-tumor immune response, cancer susceptibility and prognosis. Since PD-1 and PDL-1 have been considered as important genetic risk factors in cancer development and their functions can be affected by polymorphic sites, we investigated the effects of PD-1 rs2227981, rs2227982, rs36084323 and PDL-1 rs2282055, rs822336 gene polymorphisms on colorectal cancer (CRC) risk and prognosis in Turkish subjects. Methods and results Our study group consisted of 5-FU or Capacitabine prescribed CRC diagnosed patients and healthy controls. Genotype analyses of PD1 and PDL-1 polymorphisms were performed with Agena MassARRAY platform. rs36084323 CT genotype frequency was found to be higher in controls compared to cases (p C polymorphism might be useful in predicting CRC prognosis. PDL-1 rs2282055 T > G polymorphism might be useful in predicting both CRC risk and prognosis. Further studies should be conducted in larger and different populations to clear the roles of PD-1 and PDL-1 polymorphisms in CRC risk and prognosis.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; Colorectal cancer; Immune check point; PD-1; PDL-1; rs36084323; rs822336; rs2282055; CELL LUNG-CANCER; INDUCED EXPRESSION; IMMUNE ESCAPE; BREAST-CANCER; TUMOR-CELLS; PD1 GENE; SUSCEPTIBILITY; PD-1/PD-L1; CHILDREN; PATHWAY